PREVALENCE OF INTERNAL HELMINTH PARASITES OF Bagrus bayad IN KAFINCHIRI DAM, KANO STATE, NIGERIA - MUSA, M. I; OYEGBILE, B; MIGA, H.I.; ADOKE, I.Y; TAHIR, M.A. (Nigerian Journal of Fisheries, 2019)
This study was conducted to determine the prevalence of the internal helminth parasites of Bagrus bayad in kafinchiri dam Kano State, Nigeria. A total of 130 samples were subjected to examination for internal helminths parasites, lengths and weights of the fishes were measured prior to dissection and parasites recovered were identified. Result indicates that sixty two of the fish examined were infected with various species of helminth, which includes nematoda 50.42%, cestoda 19.75%, trematoda 28.11%, monogenea 10.92% and acanthophela7.14%,it was observed that fishes with standard length range of 21-30 (46.64%) were more infected than those of 11-20 (33.19%), 31-40 (18.07) and 41-50 (2.10 %). The highest prevalence of infection (76.47%) was recorded in fishes with body weight of 100-499g.The female fish had the highest percentage prevalence 34.61% while the males had 13.07% prevalence. The result of the study indicate that the association (p<0.05) between the prevalence of infection, sex, length and weight of the host was not statistically significant. In conclusion individuals with habit of consuming raw or partially cooked fish are at higher risk of becoming infected by Zoonotic parasites. Therefore awareness and control activities should be conducted in and around the reservoir.